Removal of ferrum from aques solution by using dried water hyacinth (Eichhornia crassipes) - Mohd Izzat, Siswo (2008)
The used of nonliving aquatic plants for the removal of toxic heavy metals as biosorbent has been study recently. The objective of this study is to investigate the capability of Eichhornia crassipes as the biosorbent in removal of ferrum from aqueous solution in laboratory scale. Biosorbent dosage, contact time, temperature and pH were chose as the parameters for this study. The experiment was carried out in conical flask with initial concentration of ferrum solution was 10 mg/L and then agitated in orbital shaker at 175 rpm. HACH spectrophotometer was used to measure the final concentration of the ferrum solution. Increasing the biosorbent dosage result more surface area for ferrum ions to bind with functional groups exist in biosorbent. The removal of ferrum increased in early stage and the optimum contact time was 60 minutes. Prolonged the contact time in this study, do not give better result for removal of ferrum. Optimum temperature was at 25oC and removal of ferrum decreased by increasing the temperature because it can damage the binding site in biosorbent. Competition with H+ will occur at acidic condition and at alkaline condition cause the precipitation of ferrum. Optimum removal of ferrum was achieved at pH 6. As the conclusion, water hyacinth (Eichhornia crassipes) is suitable for development of efficient biosorbent for the removal of ferrum from wastewater stream.